Dynamic Evaluation of Balanced Scorecard Using Fuzzy Knowledge Based Representation - Palominos-Villavicencio, F (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper presents a model that allows the dynamic evaluation of Balanced Scorecard (BSC) using fuzzy knowledge based representation. BSC has proved being a powerful tool for management that allows connecting current actions to future strategic objectives considering measures based on indicators and inductors. BSC translates business vision and mission into a set of actions guided by strategies and classifies them into four axes according to their perspective: financial, processes, customer and learning and growth. A strategic map of cause and effect relationships is generated, showing the relationships between a set of objectives and/or indicators, classified according to the perspectives to which they belong; knowing these cause-effect relationships is important for engineering management in order to provide an adequate management, coordination and control framework for business development. Nevertheless, this approach does not consider: existing dynamics between perspectives of the BSC; order and priority of the connection between axes; degrees of influence between axes; particular state of each axe and state of the system on the basis of the combination of the diverse states of the axes; positive or negative influences between axes. This work also provides an application of these concepts in a Port Community, building a conceptual map of fuzzy relations represented by a diffuse interval knowledge base matrix based in expert knowledge. © 2018 IEEE.